Maximization Network Throughput based on Maximal Flow for Single-Source Two-Destinations Multicast - Huanlin Liu; Ruiyan Li; Liang Qin; Sheng Huang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
For guaranteeing all multicast destination nodes receiving the source information with their maximal flow respectively and obtaining the network maximal throughput, a heuristic algorithm based on network coding, Maximal Flow for Single-source Two-destinations Multicast (MFSTM) is proposed to maximize the network throughput. By calculating the each destination’s maximal flow, the number of link-disjoint paths which equals to destination’s maximal flow, are searched for each destination to construct the network coding graph. A heuristic algorithm based on network coding is designed to delete the redundant link in the network coding graph and guarantee the network throughput maximization. Comparing the traditional maximal multicast stream algorithm based on network coding, the simulation results show that the MFSTM algorithm makes two destinations receive the information at the speed of their maximal flow respectively, and decode the source node information at each destination node successfully.